Default Activation and Nuclear Translocation of the Plant Cellular Energy Sensor SnRK1 Regulate Metabolic Stress Responses and Development. Issue 7 (13th May 2019) - Ramon, Matthew; Dang, Tuong Vi T.; Broeckx, Tom; Hulsmans, Sander; Crepin, Nathalie; Sheen, Jen; Rolland, Filip
Abstract : Plants appear to have modified the ancient and highly conserved eukaryotic energy sensor to better fit their unique lifestyle and more effectively cope with changing environmental conditions. Abstract: Energy homeostasis is vital to all living organisms. In eukaryotes, this process is controlled by fuel gauging protein kinases: AMP-activated kinase in mammals, Sucrose Non-Fermenting1 (SNF1) in yeast ( Saccharomyces cerevisiae ), and SNF1-related kinase1 (SnRK1) in plants. These kinases are highly conserved in structure and function and (according to this paradigm) operate as heterotrimeric complexes of catalytic-α and regulatory β- and γ-subunits, responding to low cellular nucleotide charge. Here, we determined that the Arabidopsis ( Arabidopsis thaliana ) SnRK1 catalytic α-subunit has regulatory subunit-independent activity, which is consistent with default activation (and thus controlled repression), a strategy more generally used by plants. Low energy stress (caused by darkness, inhibited photosynthesis, or hypoxia) also triggers SnRK1α nuclear translocation, thereby controlling induced but not repressed target gene expression to replenish cellular energy for plant survival. The myristoylated and membrane-associated regulatory β-subunits restrict nuclear localization and inhibit target gene induction. Transgenic plants with forced SnRK1α-subunit localization consistently were affected in metabolic stress responses, but their analysis also revealed key roles for nuclear SnRK1 in leaf and root growth and development. Our findings suggest that plants have modified the ancient, highly conserved eukaryotic energy sensor to better fit their unique lifestyle and to more effectively cope with changing environmental conditions.